Quran stories for little hearts: the delightful gardens (goodwordkidz puzzles) - Khan, Saniyasnain (Goodword kidz New Delhi, 2004)
Engage young minds with a collection of fun puzzles set in enchanting gardens. Each activity encourages creativity and critical thinking while introducing children to the beauty of nature. Perfect for sparking curiosity and a love for exploration.